Impact of the Shuangfengsi reservoir on VP broadband tiltmeter observations at Chengde station - Yaya Guo; Keliang Zhang; Yulin Zhang; Junfeng Ren; Donghui Yang (地震科学进展, 2025)
Since its installation, the VP broadband tiltmeter at Chengde station has exhibited a long-term trend of northward tilt along the north-south (NS) axis and westward tilt along the east-west (EW) axis. However, during July to August 2021, both components showed a marked acceleration in tilting, with rates approximately four times higher than the long-term average. During the same period, the nearby Shuangfengsi reservoir, located about 10 km northeast of the station, was being filled and reached its maximum water level on August 24, 2021. This study analyzes the correlation between the inclinometer data and changes in reservoir capacity and further quantifies the resulting crustal deformation using a non-uniform surface load model. Correlation analysis revealed a strong relationship between variation in the VP broadband tiltmeter data and changes in reservoir capacity. Model calculations indicated that the reservoir filling resulted in a maximum crustal subsidence of 0.4421 mm, with corresponding northward tilt of 0.1179 mm and eastward tilt of 0.0882 mm. These values are consistent with the observations recorded by the VP broadband tiltmeter. A similarly strong correlation was also observed between the tiltmeter data and reservoir capacity changes in 2022. The findings suggest that recent annual variation trends observed by the VP broadband tiltmeter at Chengde station are primarily attributable to loading effects from the Shuangfengsi reservoir. By quantitatively comparing modeled ground tilt induced by reservoir impoundment with the tiltmeter observations, this study effectively rules out tectonic origins such as earthquake precursors. These results help prevent potential misinterpretation of the data and provide a valuable example of how non-tectonic influences should be considered in the anomaly analysis used for earthquake forecasting.